From the guest editors - Urszula Ledzewicz; Eugene Kashdan; Heinz Schättler; Nir Sochen (Mathematical Biosciences and Engineering)
The editors of this special issue of Mathematical Biosciences and Engineeringwere the main organizers for the First International Workshop Mathematical Methods in System Biology, that took place on January 4-7, 2010 at Tel Aviv University in TelAviv, Israel. The workshop, initially planned as a small meeting,was an overwhelming success with 170 participants from Israel, theUS, Canada and Europe. It included about 100 presentations: invitedtalks, special sessions dedicated to application of mathematicaltools to various areas in biology and poster sessions which gavegraduate students and young scientists a stage to present theirresearch. We managed to attract a good mix of mathematicians workingon biological and medical applications with biologists and medicaldoctors interested to present their challenging problems and to findmathematical tools for their solution. We would like to take theopportunity to thank the Office of International Science andEngineering of the National Science Foundation and the Society forMathematical Biology for their support in bringing US participantsto this event. Thanks are also due to the Vice-President forResearch and Development of Tel Aviv University, the Faculty ofExact Sciences and its Dean Prof. Haim Wolfson, and the School ofMathematical Sciences for their help with covering local expenses.Special thanks are coming to the supporting team of students,postdocs and administrative staff for their incredible contributionto the success of the workshop. For more information please click the “Full Text” above.